Development and Validation of a Local Wisdom-Based Ecoliteracy Instrument for Indonesian University Students - Anas, Muh.; Al-Muhdhar, Mimien Henie Irawati; Rahayu, Sofia Ery (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Ecoliteracy integrates ecological and sustainability principles into education, emphasizing the interconnection between humans and the environment while incorporating local wisdom and traditional knowledge. This approach provides a comprehensive perspective that bridges environmental education with cultural and ethical dimensions. The present study aimed to develop and validate an ecoliteracy instrument based on local wisdom specifically for university students in Indonesia. A total of 326 students participated in this study. The instrument development followed three stages: (1) creation of dimensions and items with expert validation, (2) Exploratory Factor Analysis (EFA) and data reduction, and (3) internal consistency testing through Confirmatory Factor Analysis (CFA). The final instrument comprised 28 items across six dimensions: (1) Spiritual Values and Sacredness of Nature, (2) Traditional Sustainability Practices, (3) Togetherness and Community, (4) Folklore and Local Knowledge, (5) Environmental Ethics, and (6) Contextual Adaptation. The instrument demonstrated strong validity and reliability: KMO = 0.849, CFA confirmed a six-factor model with excellent fit (CFI = 0.956, SRMR = 0.031), and Cronbach’s alpha ranged from 0.687 to 0.990 across dimensions. The instrument employs multiple-choice questions to assess ecological knowledge, awareness, attitudes, and sustainable behavior, providing a practical and culturally relevant tool. These results indicate that the developed instrument is a reliable, valid, and contextually appropriate tool for evaluating the implementation of ecoliteracy in higher education, contributing to both academic assessment and the promotion of environmentally responsible behavior among students.